2023
DOI: 10.3390/v15122449
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and Interspecies Transmission of Cluster 3 Tembusu Virus Strain TMUV HQ-22 Isolated from Geese

Qing Yang,
Yingying Ding,
Weiping Yao
et al.

Abstract: Since 2010, the Tembusu virus (TMUV) has been highly prevalent in China, causing significant economic losses to the poultry industry. In 2022, a suspected outbreak of TMUV occurred at a goose farm located in Anhui Province. A strain of TMUV, TMUV HQ-22, was isolated from the infected geese. Phylogenetic analysis using the E gene of the HQ-22 strain demonstrated its affiliation with cluster 3, a less commonly reported cluster in comparison to the main circulating cluster, cluster 2. Through a comparison of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…While some DTMUV detection methods and vaccine formulations have been successfully launched in the domestic market, effectively curbing the spread and prevalence of certain strains, it is important to note that DTMUV belongs to the class of RNA viruses. RNA viruses have the propensity to mutate within the host environment, potentially leading to the ineffectiveness of existing detection methods and vaccines [11,15,30,147]. Additionally, with diverse transmission routes and a wide range of hosts, there is a potential risk of zoonotic transmission [11,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While some DTMUV detection methods and vaccine formulations have been successfully launched in the domestic market, effectively curbing the spread and prevalence of certain strains, it is important to note that DTMUV belongs to the class of RNA viruses. RNA viruses have the propensity to mutate within the host environment, potentially leading to the ineffectiveness of existing detection methods and vaccines [11,15,30,147]. Additionally, with diverse transmission routes and a wide range of hosts, there is a potential risk of zoonotic transmission [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, most strains isolated in Thailand and a small number from China belong to Cluster 2.a, while most isolates from China are assigned to Cluster 2.b. In recent years, two different research groups have identified a new cluster called Cluster 3 within the TMUV group, which collects virus isolates from China and Thailand [15,[30][31][32][33] (Figure 2).…”
Section: Genomic Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations